Criminalization/assimilation : Chinese/Americans and Chinatowns in classical Hollywood film - Gates, Philippa, 1973- (Rutgers University Press, 2019)
Criminalization/Assimilation traces how Classical Hollywood films constructed America's image of Chinese Americans from their criminalization as unwanted immigrants to their eventual acceptance when assimilated citizens, exploiting both America's yellow peril fears about Chinese immigration and its fascination with Chinatowns. Philippa Gates examines Hollywood's responses to social issues in Chinatown communities, primarily immigration, racism, drug trafficking, and prostitution, as well as the impact of industry factors including the Production Code and star system on the treatment of those subjects. Looking at over 200 films, Gates reveals the variety of racial representations within American film in the first half of the twentieth century and brings to light not only lost and forgotten films but also the contributions of Asian American actors whose presence onscreen offered important alternatives to Hollywood's yellowface fabrications of Chinese identity and a resistance to Hollywood's Orientalist narratives.